The Thing about Chemistry: Investigating the Fundamental Chemistry Skills of Biology Education Students at Bielefeld University - Claas Wegner; Rachel LeeAnn Bruneman; Antonia Steffen (Science Education International, 2019)
Although fundamental chemistry acts as a prerequisite for fully comprehending imperative aspects of biology, Bielefeld University is one of three universities in North Rhine-Westphalia, Germany that does not require majors or minors in biology education to complete classes in general chemistry, before fulfilling graduation requirements. A study was utilized to determine to what extent graduate students possess the chemistry skills essential for teaching the state-mandated biology curriculum. The assessed graduate students consisted of individuals with and without chemistry as their second elected subject. The chemistry skills of the individual graduate students were measured with a non-standardized knowledge test. The results of each test were computed using an evaluation form and specified point system. Results revealed that the majority of the graduate students without chemistry as their second elected subject possessed an insufficient (e.g., poor and failing) level of understanding for fundamental chemistry, characteristically essential for instructing biology lessons. The findings in this study and in previous research have established grounds for discussing potential methods of intervention and further investigation of this field, to better prepare biology education students for their teacher training and future careers.